2014
DOI: 10.3171/2014.3.jns132537
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage risks and functional outcomes of untreated brainstem cavernous malformations

Abstract: Object Cerebral cavernous malformations have been studied widely, but the natural history of brainstem cavernous malformations (CMs) is not well defined, and hemorrhages caused by brainstem CMs are devastating. The goal of this study was to quantify the hemorrhage risks and functional outcomes of patients with brainstem CMs. Methods This prospective, longitudinal, cohort study included patients with brainstem CMs diagnosed between 1985 and 2012. The clinical courses of all patients were recorded. Predictors o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 27 publications
0
75
2
Order By: Relevance
“…Once cavernomas bleed, the rebleeding rate increases to 45% per person per year [3,5,16]. The optimal treatment for these lesions remains a matter of debate, and how to identify cavernomas that are at high risk of developing hemorrhage recurrences or producing severe neurological deficits remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once cavernomas bleed, the rebleeding rate increases to 45% per person per year [3,5,16]. The optimal treatment for these lesions remains a matter of debate, and how to identify cavernomas that are at high risk of developing hemorrhage recurrences or producing severe neurological deficits remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent hemorrhage was defined using the same criteria described before for the first episode of hemorrhage, but if the patient had a residual deficit of the first event, the worsening of this deficit was also included [5,14]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated bleeding and rebleeding rates for brainstem CMs range from 0.5% to 6% and 5% to 60% per patient-year, respectively. 10,25,26,35 The management of brainstem CMs remains challenging due to a high degree of potential morbidity and mortality with and without treatment and specifically due to the eloquence of the perilesional anatomy. Resection is fraught with significant rates of permanent neurological deterioration, including for brainstem CMs reaching the pial surface.…”
mentioning
confidence: 99%
“…Patients presenting with a hemorrhage have significantly higher rates of rehemorrhage compared to patients presenting due to incidental findings. 3,4 Flemming et al found that patients presenting with hemorrhage had an overall annual rate of hemorrhage of 6.19% compared to patients presenting without hemorrhage of 0.33%. With increasing use of MR imaging, the percentage of cavernous malformations found incidentally approaches 40%.…”
Section: Stereotactic Radiosurgery For Management Of Cavernous Malformentioning
confidence: 99%